Composition of crystals of palm olein formed at room temperature - Swe, P.Z.; Che Man, Y.B.; Ghazali, H.M. (AOCS Press, 1995)
The composition of purified plam olein crystals formed at room temperature (25°C) was identified in this study. Two peaks were obtained when the crystals were analyzed by reverse-phase high-performance liquid chromatography (RP-HPLC). The retention times of these peaks suggested that they were not triglycerides. Gas-liquid chromatography of fatty acid methyl ester analysis of the crystals showed the presence of C16, C18:0, and C18:1 fatty acids. Further analysis by gas-liquid chromatography of carbon number, after collecting the fractions from RP-HPLC, concluded that the major peak A was 1,3-dipalmito-glycerol. The minor peak B was tentatively identified as 1-palmito-3-stearo-glycerol and/or 1-palmito-3-oleo-glycerol due to unavailability of respective standard glycerides. The differential scanning calorimetry thermogram of the crystals show that A and B were indeed the high melting glycerides, with melting and crystallization points of 70.4 and 53.8°C, respectively.